Alternative Reference Point based Handover Algorithm for LTE High-speed Rail - Rui Zhang; Muqing Wu; Yifan Zhang; Linlin Luan (Institute of Advanced Engineering and Science, 2014)
A new fast handover algorithm for LTE high-speed rail networks is proposed in this paper. In railway environment, the motion direction and the GPS information of the train can be obtained at any time. Moreover, the neighbor cell that the UE will go through can be precognitive. The above information are utilized to bring forward a fast handover scheme in this paper, which can give a set of alternative reference points appropriate to trigger handover procedure instead of the measured information in A3 event based scheme. The proposed algorithm can evidently reduce time latency and accordingly shorten the necessary overlapping area of handover procedure, and the simulation results show that it has better performance than typical A3 event based handover algorithm in high-speed rail environment. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4498